2009
DOI: 10.1590/s0100-204x2009000100014
|View full text |Cite
|
Sign up to set email alerts
|

Valor nutritivo da forragem e produção animal em pastagens de Brachiaria brizantha

Abstract: Resumo -O objetivo deste trabalho foi avaliar a produção animal e sua relação com as características dos pastos de Brachiaria brizantha cultivares Marandu, Xaraés e Piatã. O delineamento experimental foi o de blocos ao acaso, com três tratamentos e duas repetições. Os piquetes com 2 ha foram subdivididos em dois e submetidos ao pastejo alternado, com 28 dias de utilização e 28 dias de descanso. Foram utilizados três novilhos teste, por piquete, e novilhos reguladores para manter resíduos pós-pastejo em torno d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
3
17

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 10 publications
5
42
3
17
Order By: Relevance
“…Piatã was similar to that reported by Nantes et al (2013), but lower (770 g) than that reported by Euclides et al (2009). The lower performance observed in the present study cannot be attributed to the herbage nutritive value because the average percentages of CP and IVOMD (8.8 and 55.3%, respectively) for the wet season (Table 3) were higher than those reported by Euclides et al (2009). However, in the study conducted by Euclides et al (2008), the canopy structure was more favorable for animal grazing than that of the present study (Table 2), with 41.3% leaves and a leaf:stem ratio of 1.62.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Piatã was similar to that reported by Nantes et al (2013), but lower (770 g) than that reported by Euclides et al (2009). The lower performance observed in the present study cannot be attributed to the herbage nutritive value because the average percentages of CP and IVOMD (8.8 and 55.3%, respectively) for the wet season (Table 3) were higher than those reported by Euclides et al (2009). However, in the study conducted by Euclides et al (2008), the canopy structure was more favorable for animal grazing than that of the present study (Table 2), with 41.3% leaves and a leaf:stem ratio of 1.62.…”
Section: Discussionsupporting
confidence: 90%
“…Piatã was similar to that reported by Nantes et al (2013), but lower (770 g) than that reported by Euclides et al (2009). The lower performance observed in the present study cannot be attributed to the herbage nutritive value because the average percentages of CP and IVOMD (8.8 and 55.3%, respectively) for the wet season (Table 3) were higher than those reported by Euclides et al (2009).…”
Section: Discussionsupporting
confidence: 83%
“…5) no ganho médio diário de peso (GMD. A média de ganho de peso foi semelhante à encontrada por Euclides et al (2009) em pastos de capim-marandu, durante três períodos das águas. Independentemente da altura de manejo, o valor nutritivo da lâmina foliar foi satisfatório e condizente com a produção por animal  11% de PB e 60% de DIVMO.…”
Section: Arqunclassified
“…The importance of Brachiaria genus species is due to their adaptability to acid and poor fertile soils, elevated capacity of dry matter production and nutritional quality (Euclides et al, 2009;Timossi et al, 2007). These grasses are largely cultivated on several production systems, for animal feeding or as suppliers of straw to the system.…”
Section: Introductionmentioning
confidence: 99%